Validity and Reliability of a Glucometer Against Industry Reference Standards. (January 2014) - Salacinski, Amanda J.; Alford, Micah; Drevets, Kathryn; Hart, Sarah; Hunt, Brian E.
As an appealing alternative to reference glucose analyzers, portable glucometers are recommended for self-monitoring at home, in the field, and in research settings. The purpose was to characterize the accuracy and precision, and bias of glucometers in biomedical research. Fifteen young (20-36 years; mean = 24.5), moderately to highly active men (n = 10) and women (n = 5), defined by exercising 2 to 3 times a week for the past 6 months, were given an oral glucose tolerance test (OGTT) after an overnight fast. Participants ingested 50, 75, or 150 grams of glucose over a 5-minute period. The glucometer was compared to a reference instrument. The glucometer had 39% of values within 15% of measurements made using the reference instrument ranging from 45.05 to 169.37 mg/dl. There was both a proportional (−0.45 to −0.39) and small fixed (5.06 and 0.90 mg/dl) bias. Results of the present study suggest that the glucometer provided poor validity and reliability results compared to the results provided by the reference laboratory analyzer. The portable glucometers should be used for patient management, but not for diagnosis, treatment, or research purposes.